Bioecological characteristics of Sophora Japonica. - Tuychiyeva Khilola Zokirjon kizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In this article, the bioecological characteristics of the acclimatized ornamental tree Japanese saphora, including the vegetation period of Japanese saphora, its resistance to any soil conditions, are mainly recommended as an ornamental tree, and its useful properties in medicine and folk medicine are highlighted.